Applying the Andersen behavioral model to the medication therapy management program: an approach for improving medication safety in older adults - Fu, Yu-Hua; Castora-Binkley, Melissa; Coe, Antoinette B.; Snyder, Margie E.; Cooke, Catherine E.; Vogel, Carlyn E.; Hines, Lisa; Lyles, Alan; Brandt, Nicole (Frontiers in Public Health, 2024)
Medication therapy problems (MTPs) are common among older adults and are associated with considerable morbidity, mortality, and healthcare costs. The Medicare Part D Medication Therapy Management (MTM) program, which includes Comprehensive Medication Reviews (CMRs), Targeted Medication Reviews (TMRs), and guidance on safe medication disposal, is designed to optimize therapeutic outcomes and reduce adverse events by addressing MTPs. Although this program has demonstrated success in reducing MTPs, its utilization remains low, with ongoing concerns about service access disparities, patient satisfaction, and long-term health outcomes. This perspective paper applies the Andersen Behavioral Model (ABM) to the Medicare Part D MTM program to enhance understanding of factors influencing service utilization and impact among older adults. The ABM provides a structured framework to examine how macro-and micro-level factors shape health behaviors and outcomes. By applying ABM framework to MTM, this paper highlights essential research directions to generate rigorous evidence for program evaluation, inform policy adjustments, and make targeted recommendations for improving MTM within the U.S. healthcare system. Furthermore, this work has potential implications for global programs aimed at enhancing medication safety by addressing MTPs and optimizing medication use.